2015
DOI: 10.1007/s00248-015-0664-x
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Effects of Wildfire on Foliar Endophyte Communities in Montane Forest Trees

Abstract: Plants in all terrestrial ecosystems form symbioses with endophytic fungi that inhabit their healthy tissues. How these foliar endophytes respond to wildfires has not been studied previously, but is important given the increasing frequency and intensity of severe wildfires in many ecosystems, and because endophytes can influence plant growth and responses to stress. The goal of this study was to examine effects of severe wildfires on endophyte communities in forest trees, with a focus on traditionally fire-dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 99 publications
0
34
0
Order By: Relevance
“…We tested leading hypotheses about the effects of climate, geographic distance, and host identity using this system, and for the most part, found them to be strong predictors of differences in FEF communities between samples -even when the measurements were taken at relatively coarse resolution (Table 1). We found that elevation (Zimmerman & Vitousek, 2012), host plant phylogenetic difference (Unterseher et al, 2012;Kembel & Mueller, 2014;Massimo et al, 2015;Huang et al, 2016;Vincent et al, 2016), spatial (U'Ren et al, 2012), and habitat type (Jumpponen & Jones, 2009Kato et al, 2017) hypotheses all held true to varying extents in our analysis (Figure 3). We found limited (but significant) support for the hypothesis that rainfall structures FEF communities (U'Ren et al, 2012;Zimmerman & Vitousek, 2012), and we also found that evapotranspiration, which had not been previously considered as an important variable, was a significant predictor of difference in FEF communities across the Hawaiian archipelago.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We tested leading hypotheses about the effects of climate, geographic distance, and host identity using this system, and for the most part, found them to be strong predictors of differences in FEF communities between samples -even when the measurements were taken at relatively coarse resolution (Table 1). We found that elevation (Zimmerman & Vitousek, 2012), host plant phylogenetic difference (Unterseher et al, 2012;Kembel & Mueller, 2014;Massimo et al, 2015;Huang et al, 2016;Vincent et al, 2016), spatial (U'Ren et al, 2012), and habitat type (Jumpponen & Jones, 2009Kato et al, 2017) hypotheses all held true to varying extents in our analysis (Figure 3). We found limited (but significant) support for the hypothesis that rainfall structures FEF communities (U'Ren et al, 2012;Zimmerman & Vitousek, 2012), and we also found that evapotranspiration, which had not been previously considered as an important variable, was a significant predictor of difference in FEF communities across the Hawaiian archipelago.…”
Section: Discussionmentioning
confidence: 65%
“…Unlike elevation, rainfall, and evapotranspiration, which have each been used to model FEF community dissimilarity by only a handful of studies, patterns of host association in FEF communities have been thoroughly documented (Unterseher et al, 2012;Kembel & Mueller, 2014;Massimo et al, 2015;Huang et al, 2016;Vincent et al, 2016;Kato et al, 2017). Thus, it is not surprising that phylogenetic difference among host plants was a statistically significant predictor of FEF community dissimilarity in our analysis (Figure 3).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…and "Ascomycota sp.". Accordingly, many endophyte studies report endophyte taxa that are often unidentified to species or even genus , U'Ren et al 2012, Huang et al 2016).…”
Section: Problems Identifying Endophytesmentioning
confidence: 99%
“…These results provide insight into the complex life histories of conifer needle endophytes and present a straightforward strategy to identify unknown endophyte cultures and sequences by considering the biology and ecology of the whole fungus.INTRODUCTIONIncreasing research interest in the biodiversity and functional ecology of endophytes has stimulated extensive cultivation and sequencing efforts to investigate endophytes from a wide range of host plants worldwide. However, in such studies most representative endophyte taxa are often unidentified to species or genus, U'Ren et al 2012, Huang et al 2016). Endophytes are difficult to identify because of a lack of taxonomically informative cultural characters and a paucity of relevant reference sequences in databases such as NCBI GenBank or UNITE(Kõljalg et al 2005).…”
mentioning
confidence: 99%